Nosocomial infections in a Surgical Floor of the General Ba’qubah Hospital; Iraq - Al-Kharkhi, Mohammed A.; Mohammed Zeiny, Sarmad M.; Ali, Samara M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Prevention against nosocomial infection is an important issue of health care field and considered a challenge of patients’ since it reflects its effect on their quality of life. This due to that it will lead in most cases to prolonged hospitalization and also more cost. Objective: To determine the prevalence of different types of nosocomial infection and to demonstrate the association of different risk factors (hospital environment, workers, visitors) with nosocomial infection. Patients: this study was carried out in eleven months at Ba’quba general Hospital; Iraq. A total of 81 clinical specimens (urine, pus from abscess , burn swab, nasal swab, ear swab and wound swab) taken from surgical patients,102 specimens from hospital workers,50 specimens from patient visitors,335 specimens from hospital environment and 64 specimens from 18 newly admitted patient were studied. Methods: all microorganisms which were isolated from patients, workers, visitors control group and environment were identify using standard bacteriological and mycological methods. Results: the present findings demonstrates that the percentage of nosocomial infection (N.I) types found to be highest with urinary tract infections 21 (40%), followed by surgical site infections 19 (35.8%) and respiratory tract infection 12 (23%). Conclusion: most of the isolated microorganisms were resistant to antibiotics and most of them have ability to produce β-lactamase enzyme